Diagnostic and Management Challenges of Subclavian Artery Aneurysms in the Setting of Methicillin-Resistant Staphylococcus aureus Bacteremia and Upper Extremity Deep Vein Thrombosis - Lifei Zhu; Milan Regmi; Syed S. Fatmi (Journal of Vascular Diseases)
Background: Mycotic aneurysms of the subclavian artery are infrequent and pose significant diagnostic challenges, particularly in the context of recurrent methicillin-resistant Staphylococcus aureus (MRSA) bacteremia. The concomitant presence of upper extremity deep vein thrombosis (UEDVT) further complicates the management of bleeding risk and the necessity for anticoagulation therapy. Methods: This report discusses a 75-year-old male patient with a medical history of lung and skin cancer undergoing immunotherapy who presented with a swollen and painful right arm. Ultrasound examination identified deep vein thrombosis in the right axillary and basilic veins, and blood cultures confirmed MRSA infection. Subsequent imaging revealed bilateral subclavian artery aneurysms with contained ruptures involving previously placed stent grafts. Emergent endovascular interventions were performed to prevent catastrophic hemorrhage. Results: Despite the initial interventions, concerns regarding infected stent grafts persisted due to ongoing MRSA bacteremia and the presence of an endoleak. The complexity of balancing anticoagulation for DVT with the risk of aneurysm rupture necessitated the patient’s transfer to a tertiary care center for potential open surgical debridement. Conclusions: This case underscores the diagnostic and therapeutic challenges associated with the simultaneous occurrence of vascular infection, thrombosis, and aneurysmal pathology. Although emergency endovascular repair provided temporary hemostatic control, definitive management may require graft removal if stent infection is confirmed. Optimal care in such complex clinical scenarios demands a multidisciplinary approach and may necessitate advanced surgical interventions.